A Thermal Conductivity Predictive Method of Graphene Epoxy Nanocomposites. (August 2020) - Wang, Danyong; Zhang, Haiyun; Wei, Huazhen; Li, Shuhu
Abstract: Interfacial interaction between flaked graphene and epoxy was the key element of effecting whether graphene as nanofillers could improve some of the properties of epoxy. Based on really materials and applied manufacturing process, a new kind of a thermal conductivity predictive method for graphene epoxy nanocomposites which could compute and analyze thermal conductivity of any content ratio of graphene in the epoxy with only one content ratio was built in order to provide theoretical foundations for design and property of graphene epoxy nanocomposites. According to practically different materials system and corresponding manufacturing processes, few experiments which only needed thermal conductivity of one random content-ratio graphene epoxy nanocomposites were made to predict effective thermal conductivity of any other content ratio of graphene epoxy nanocomposites under the same manufacturing processes by obtaining experimental constants based on numerical progressive iterative approximation method and compute the above experimental constants as basic materials parameters so as to build the whole analysis model in the next step. An excellent agreement was found between data obtained from this study and the experiment.